1993
DOI: 10.1200/jco.1993.11.4.704
|View full text |Cite
|
Sign up to set email alerts
|

High-dose etoposide and melphalan, and autologous bone marrow transplantation for patients with advanced Hodgkin's disease: importance of disease status at transplant.

Abstract: Etoposide and melphalan is an effective and well-tolerated intensive therapy regimen in advanced Hodgkin's disease. Patients in complete remission after conventional-dose salvage therapy transplanted with this regimen enjoy superior long-term DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
93
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 0 publications
5
93
0
3
Order By: Relevance
“…In refractory patients pooled with complete responders (Ͻ12 months), high-dose chemotherapy with reinfusion of HSC yielded CR rates of 40-80% with approximately 40% of patients free of disease at 3 years. [15][16][17][18][19][20][21][22][23][24][25] High-dose chemotherapy with BMT is particularly appealing since some patients with disease refractory to conventional-dose chemotherapeutic regimens can be cured. 16,24,25 The BNLI compared standard salvage chemotherapy to high-dose chemotherapy with bone marrow transplantation and found higher event-free survival in the high-dose chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In refractory patients pooled with complete responders (Ͻ12 months), high-dose chemotherapy with reinfusion of HSC yielded CR rates of 40-80% with approximately 40% of patients free of disease at 3 years. [15][16][17][18][19][20][21][22][23][24][25] High-dose chemotherapy with BMT is particularly appealing since some patients with disease refractory to conventional-dose chemotherapeutic regimens can be cured. 16,24,25 The BNLI compared standard salvage chemotherapy to high-dose chemotherapy with bone marrow transplantation and found higher event-free survival in the high-dose chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…31 Of the various prognostic factors identified for long-term disease-free survival in high-dose chemotherapy trials, one of the most frequently found is the chemosensitivity of HD at the time of transplantation. 16,24,[27][28][29][30] Salvage chemotherapy before BMT could therefore play an important role in the curability of patients with primary refractory or relapsed HD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations